Therapeutic Effect of Amomum villosum on Inflammatory Bowel Disease in Rats - Chen, Zhu; Ni, Wanye; Yang, Caixia; Zhang, Ting; Lu, Shanhong; Zhao, Ronghua; Mao, Xiaojian; Yu, Jie (Frontiers in Pharmacology, 2018)
Background: Amomum villosum Lour., a herbaceous plant in the ginger family, has been proven to be effective in treating gastrointestinal diseases. It has been listed in the Chinese Pharmacopeia as a legal source of Amomi Fructus. In our previous study, we demonstrated that treatment with extracts of A. villosum prevented the development and progression of intestinal mucositis. In the current study, we aimed to verify and explain the potential beneficial effects of A. villosum on inflammatory bowel disease (IBD). Methods: The effect of water extracts (WEAV) and volatile oil of A. villosum (VOAV) were evaluated on the immunological role of T lymphocytes and intestinal microecology in IBD rats induced with 2, 4, 6-trinitrobenzenesulfonic acid (TNBS). Body weight, food intake, colon length/weight, disease activity index (DAI) as well as tissue damage scores were evaluated. The inflammatory response to IBD was assessed by measuring the expression of myeloperoxidase (MPO), interleukin (IL)-17 (IL-17), interferon-γ (IFN-γ), IL-10, tumor necrosis factor-α (TNF-α), and transforming growth factor-β (TGF-β). The percentage of regulatory CD4+ T cells in rat spleen was measured by flow cytometry and effects on the microbial community were evaluated by 16S rDNA gene sequencing. Results: All TNBS-induced rats showed typical clinical manifestations of IBD. IBD rats in the WEAV and VOAV treatment groups were effective in relieving body weight and appetite loss. Middle and high dosage of VOAV and WEAV significantly reduced the DAI, and tissue damage scores, whereas colon weight/length ratio was increase. All rats in the WEAV and VOAV groups showed significantly decreased IFN-γ levels and increased levels of IL-10 and TGF-β. Moreover, we observed that the percentage of regulatory CD4+ T cells was significantly enhanced during treatment with WEAV. In addition, administration of WEAV and VOAV effectively inhibited the release of enterogenic endotoxin, increased short-chain fatty acid-producing bacteria belonging to Firmicutes and Bacteroidetes, and decreased the abundance of Proteobacteria. Conclusions: Treatment with WEAV and VOAV significantly attenuated intestinal inflammation in IBD rats, which was possibly associated with its regulation on inflammatory cytokine and CD4+CD25+FOXP3+ T cells. Moreover, WEAV and VOAV may help maintaining the balance of intestinal microecology.